2012
DOI: 10.4103/0019-557x.106420
|View full text |Cite
|
Sign up to set email alerts
|

A study on infant and young child feeding practices among mothers attending an urban health center in East Delhi

Abstract: A cross sectional study was conducted to study the diet pattern of children less than 2 years with regard to certain infant and young child feeding (IYCF) indicators. A total of 374 children less than 24 months of age coming to the immunization clinic were studied using a standard pretested and prevalidated questionnaire. Exclusive breastfeeding was followed by 57.1% of children under 6 months of age. Minimum dietary diversity, minimum meal frequency, and minimum acceptable diet were seen adequate in 32.6%, 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
72
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 0 publications
13
72
12
Order By: Relevance
“…Ergib Mekibib et al also reported from northern Ethiopia that 17.8% of mothers fed their child from four and more food groups and the result of this study is lower than findings from Kamba Woreda SNNPR was 23.3%, Delhi, India 32.6% [19,22]. The prevalence of MMF was higher than national level 4.3% and SNNPR 2.5%.…”
Section: Discussioncontrasting
confidence: 64%
“…Ergib Mekibib et al also reported from northern Ethiopia that 17.8% of mothers fed their child from four and more food groups and the result of this study is lower than findings from Kamba Woreda SNNPR was 23.3%, Delhi, India 32.6% [19,22]. The prevalence of MMF was higher than national level 4.3% and SNNPR 2.5%.…”
Section: Discussioncontrasting
confidence: 64%
“…21 Khan et al showed that 37.2% of the mothers initiated breastfeeding within one hour, which was higher compared to our study. 22 In another study Parashar M et al also found 29% of the mothers initiated breastfeeding within one hour which was higher than our study. It was found that initiation was delayed because of the presence of some beliefs and practices enforced by elder persons, such as mother-inlaw.…”
Section: Discussioncontrasting
confidence: 66%
“…19 Another study in Delhi showed that exclusive breast feeding was done by 57.0% mothers for children under 6 months of age. 20 While Joseph N et al in their study found that 41.7% mothers exclusively breastfed (EBF) their infants for 6 months. 21 On bivariate analysis of certain maternal and sociodemographic factors influencing EBF it was seen that exclusive breast feeding was significantly associated with 4 or more numbers of ANC visits, primipara mothers, higher educational status of mother, younger age and lower socioeconomic status of the mothers.…”
Section: Discussionmentioning
confidence: 98%